THE EFFECTIVENESS OF USING CHORAL READING IN IMPROVING STUDENTS’ READING COMPREHENSION AT SMP 3 TUMPAAN - Sandag, Novia Anggreani; Muntuuntu, Meity; Hampp, Paula (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research aims to determine the improvement of students’ reading comprehension in terms of finding main ideas and identifying supporting ideas in students’ of SMPN 3 Tumpaan for the 2022/2023 school year.This study used Classroom Action Research consisting of two cycles. The sample of this study consisted of 20 students’. Research obtained the data using reading tests. The research of students’ reading tests on D-test, cycle I and cycle II have significant differences in scores. There was a better improvement of students’ gains at the end of the action in the second cycle. In test D the average score of students’ is 57.5, cycle I 68.375 and cycle II 83.25. Based on the result of the analysis, it was concluded that the students’ improvement on literal comprehension in term of finding main idea and identifying supporting idea using choral reading method at the seven grade of SMPN 3 Tumpaan were improved.